Constraint-Induced Therapy as Behavior Analysis Neurorehabilitation Intervention: An Interview With Dr. Edward Taub - Iversen, Iver H. (European journal of behavior analysis, 2013)
Dr. Edward Taub has developed an effective therapy for stroke victims called Constraint-Induced Movement therapy. The foundation of this therapy is based entirely on behavior analysis principles, and intervention is a matter of applying contingencies of reinforcement for improving the movement of limbs impaired by different types of central nervous system damage. The result is a very efficacious therapy that produces large and clinically significant gains in performance that have been replicated numerous times across patients, clinics, and countries. Dr. Taub answers questions regarding the development of this therapy, which started with animal models, and offers insight into implementing behavior-analysis based treatments in medical settings.